Safety Profile of the New 5-ASA Based Compounds - Vinod K Sharma (Canadian Journal of Gastroenterology)
5-aminosalicylic acid (5-ASA) preparations were anticipated to be and generally are better tolerated than sulphasalazine. Minor side effects such as headache, dizziness, abdominal pain and nausea do occur but are not more frequent than in placebo-treated patients. Approximately 10% of patients thought to be allergic to sulphasalazine are also allergic to 5-ASA. An idiosyncratic reaction with worsening of symptoms can occur. Diarrhea is more common with olsalazine, and it is due to the effect of olsalazine itself on the small bowel. not the 5-ASA component. There are case reports of pancreatitis, pericarditis and bronchospasm, retrosternal chest pain, mild neutropenia, nephrotic syndrome and hair loss associated with 5-ASA treatment. Patients with oligospermia due to sulphasalazine have improved when switched to 5-ASA. 5-ASA enemas can cause local irritation or other effects resulting from enema tip insertion.